Health Worker's Compilance and Pregnant Women's Perceptions of The MCH Handbook : A Scoping Review - Elvira Nafiani; Zulvayanti Zulvayanti; Puspa Sari (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
The Maternal and Child Health (MCH) Handbook is a vital tool designed to enhance maternal and child health services by fostering improved communication between healthcare providers and expectant mothers. However, its effective utilization is significantly influenced by various factors, particularly the adherence of health workers to its guidelines and the perceptions held by pregnant women. This scoping review investigates the determinants affecting health workers' compliance and the engagement of pregnant women with the MCH Handbook. A systematic search of electronic databases was conducted to identify relevant studies published over the past decade, employing thematic analysis to categorize the factors impacting compliance and perceptions. Preliminary findings indicate that organizational support, training, workload, and motivation play crucial roles in health workers' adherence, while factors such as literacy levels, cultural beliefs, and previous healthcare experiences shape pregnant women's perceptions of the handbook. Recognizing these factors is essential for developing targeted interventions aimed at optimizing the handbook's use and improving maternal and child health outcomes. Moreover, the review emphasizes the urgent need for further research to establish evidence-based strategies that enhance the implementation of the MCH Handbook across diverse healthcare settings. Effective use is not solely about distribution; it requires a comprehensive understanding of the contextual factors influencing its application. By addressing the identified barriers and facilitators, stakeholders-including healthcare administrators, policymakers, and community organizations-can create tailored interventions that support health workers and empower pregnant women. Such efforts are expected to lead to improved health services and outcomes for mothers and children, highlighting the importance of a collaborative approach in maternal and child health initiatives. Prioritizing this research agenda will ensure the MCH Handbook effectively serves families from various cultural and socioeconomic backgrounds. Keyword: MCH Handbook, Health Workers' Compliance, Pregnant Women's Perceptions.